Actividad antibacteriana de especies vegetales procedentes del distrito de Cachicadán, provincia de Santiago de Chuco, región La Libertad - Polo Vidal, Milagros Elizabeth (2018)
The purpose of this report is to evaluate the antibacterial activity of five plant species from the district of Cachicadán, province of Santiago de Chuco, La Libertad region. The plant species used were Cuphea ciliata Ruiz & Pav., Myrcianthes myrsinoides (Kunth) Grifo, Clinopodium pulchellum (Kunth) Govaerts, Desmodium molliculum (Kunth) DC. and Bejaria aestuans Mutis ex L .; the strains used were Bacillus subtilis, Escherichia coli, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA). The extracts were prepared at 10% in ethanol of 45 ° G.L. The antibacterial activity was evaluated by the ratio of the minimum inhibitory concentration and the minimum bactericidal concentration (CMB/MIC). The determination of CMI was carried out by the method of microdilution in Mueller-Hinton medium and the determination of CMB by the agar diffusion method. The results of MIC of the five species under study against the four bacteriological strains are between 0.31 to 40 mg/mL and for CMB it is between the ranges of 0.63 to 40 mg/mL. Reaching the conclusion that M. myrsinoides and C. pulchellum showed bactericidal activity for the four bacteriological strains; C. ciliata only showed bactericidal activity for B. subtilis, S. aureus and MRSA; D. molliculum and B. aestuans showed bacteriostatic activity for B. subtilis and bactericidal activity for S. aureus, E. coli and MRSA